Hubungan Pengetahuan Ibu Terhadap Penggunaan Tapel Perut Pada Masa Nifas Di Desa Banyumas, Stabat 2019 - Alfi Laili (Excellent Midwifery Journal, 2019)
During the childbirth period, there will be some physiological changes happen. One of them is the involution of the uterus. In addition, during the childbirth, the mothers also gave same complaints related to the abdomen pain, tiredness, the stretch of the body, fet belly and stretch marks. The purpose of this study was to find at the relationship of mothers’ knowledge about the traditional concoction of Tapel on the usage of Tapel during the childbirth period at Banyumas Village, stabat in 2019. This study involved 30 respondents and used correlation research. The results showed that there was the relationship of the respondent’ age, education and knowledge to the usage of Tapel during the childbirth period.Keywords        : The Usage Of Tapel During The Childbirth Period, involution of the uterus.